A240 ANTIMICROBIAL LOCK SOLUTIONS FOR PREVENTION OF CENTRAL VENOUS CATHETER INFECTIONS IN PEDIATRIC PATIENTS WITH INTESTINAL FAILURE. (15th March 2019) - Gibson, B; McNiven, C; Sebastianski, M; Featherstone, R; Vandermeer, B; Persad, R; Robinson, J
Abstract: Background: Children with intestinal failure are dependent on total parenteral nutrition (TPN) via a central venous catheter (CVC) for survival. These patients require long-term use of CVCs, and are at high risk of catheter-related bloodstream infections (CRBSIs). Prevention of these infections is imperative, as they result in line removal and loss of an access site. Eventually there may be no available sites for a CVC, and a child will need an intestinal transplant. Antimicrobial locks (AML) are solutions instilled in CVCs to prevent CRBSI. Presently, there are many different solutions available, and limited evidence guiding the optimal choice, frequency, and duration of prophylactic AML solution in children with intestinal failure. A guideline for appropriate prophylactic AML use has the potential to decrease rates of CRBSIs and reduce morbidity and mortality in pediatric intestinal failure patients. Aims: In children with intestinal failure who require a CVC, does using an AML solution decrease the rate of new CRBSI? Methods: A systematic review of available literature on AMLs used for CRBSI prophylaxis in children with intestinal failure will be performed to determine the optimal AML(s) choice(s) for use in this population. Randomized and nonrandomized trials, case studies, and cohort studies that use comparator groups (including historical controls) with study participants including children (age 0–17) with intestinal failure, who have a CVC (2 days or greater) for TPN will be screened. If the data is sufficiently homogenous, both clinically and methodologically, we will pool outcomes in a meta-analysis using a DerSimonian Laird random effects model. If possible we also plan to do network meta-analyses (NMA), simultaneously pooling common outcomes across multiple interventions. Results: The primary outcomes of interest are the rate of new CRBSI with AML versus controls, as well as a comparison of each type of AML versus controls. Secondary outcomes that will be assessed include: unplanned CVC removal (all cause), CVC removal due to CRBSI, recurrence of CRBSI with the same pathogen, all adverse events/side effects attributed to antimicrobial lock solutions by the authors, development of infections with antibiotic resistance at any point (in particular resistance to antibiotics used in the AML solution), length of hospital stay attributed to CRBSI, need for intensive care, any other morbidities or outcomes that were compared in cases and controls and mortality. Conclusions: This research in progress aims to provide clinicians with guidance on the use of AML for prophylaxis of CRBSI in pediatric patients with intestinal failure. We will provide data for the efficacy of this practice and clarify which solutions have the best outcomes. Funding Agencies: None